1977
DOI: 10.1902/jop.1977.48.8.456
|View full text |Cite
|
Sign up to set email alerts
|

Plaque Removal by the Bass and Roll Brushing Techniques

Abstract: The effectiveness of plaque removal using two brushes with the Bass technique and two with the Roll method was compared in a group of 38 junior dental students using a crossover experimental design. The Bass technique was superior to the Roll method in cleaning the tooth tissue adjacent to the gingival tissue on the lingual and facial aspects, but no significant differences were found in the overall effectiveness. Cleaning of all tooth surfaces was at an unacceptable level and it is concluded that efficient to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 2 publications
1
37
0
Order By: Relevance
“…Some other studies are less conclusive, as they lack control groups and standardized instructions. Furthermore, gingivitis as an indicator of habitual oral hygiene is not assessed in these studies nor are oral hygiene skills as a premise of successful hygiene [11], [12], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies are less conclusive, as they lack control groups and standardized instructions. Furthermore, gingivitis as an indicator of habitual oral hygiene is not assessed in these studies nor are oral hygiene skills as a premise of successful hygiene [11], [12], [28], [29].…”
Section: Discussionmentioning
confidence: 99%
“…[9], [10]. The few studies directly comparing brushing techniques suffer from methodological shortcomings like lack of control groups [11], non-blinded examiners [12], [13] or confounders and missing standardization [14]. We thus decided to compare the effects of computer-based training.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, proper oral hygiene in children can be attained with the interplay of proper brushing technique and repeated learning through appropriate communication means. [10]. At 7-9 years of age the onset of the cognitive development of child helps him understand and perceive the given instructions and the required manual dexterity is also present at this younger age group.…”
Section: Discussionmentioning
confidence: 99%
“…This was in contrast to the 0.20 mm of the Oral-B40 and 0.18 mm of the Softex which were the brushes used with the Bass technique in the experiment of Gibson and Wade. 6 Robertson and Wade 11 showed that after only 2 weeks uninstructed brushing with Spa brushes of the type used in the current trial, most were worn excessively and were markedly inferior in plaque removal to Gibbs brushes of the pattern used with the Roll technique in this investigation. It may well be that such fine filament brushes are incapable of achieving plaque control regardless of the stroke used.…”
Section: Discussionmentioning
confidence: 56%
“…This evidence suggests that time spent on explaining and demonstrat ing brushing techniques is time well spent and supports the evidence of Elliott et al 5 and Gibson and Wade . 6 The degree of improvement in plaque control pro duced by the Bass method with the brush used in this investigation was more or less the same on both the lingual and facial surfaces (14 and 13% respectively) when the plaque scores after the 2-week brushing pe riod were compared with the initial scores (Table 2). Lingually, the Roll technique produced a similar de gree of improvement, 16%, but facially the benefits were more readily apparent, there being a 30% im provement on this aspect.…”
Section: Discussionmentioning
confidence: 65%